EFEKTIVITAS DAN PENGARUH BANSOS TERHADAP TINGKAT PEMENUHAN KEBUTUHAN DASAR PENDUDUK LANSIA KECAMATAN MENGWI KABUPATEN BADUNG - Pramisita, Anak Agung Dinda; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 4 (2020): VOL 9 NO 4, April 2020, PP 719 - 962, 2020)
Increasing of elderly population sometimes has a negative impact on regional development, so some social assistance is needed in supporting the welfare of these elderly citizens. The research objectives are to 1) Analyze effectiveness of social assistance for elderly in the District of Mengwi Badung Regency. 2) Analyze proportion of social assistance utilization for the elderly population. 3) Analyze is there differences in the level of fulfillment before and after social assistance is provided for elderly population. 4) Analyze differences in health status before and after social assistance is provided for the elderly population. This study used are secondary and primary data. This research is by interview and observation with 98 respondents. Analysis technique used is the effectiveness analysis technique, Wilcoxon test and McNemar Bowker test. The counclution is 1) Social Aid for the elderly population in Mengwi District Badung Regency is very effective. 2) Proportion of utilization of all social assistance funds is the most in the field of food. 3) There is a difference in the level of fulfillment before and after social assistance is provided for the elderly population. 4) There are differences in health status before and after social assistance is provided for the elderly population. Keywords: effectiveness, utilization of social assistance, basic needs, healty.